From Modernism to Neo-Modernism: A Religio-Political Context of Muhammad Abduh and Fazlur Rahman - Alfina Hidayah; Maghribi, Hamdan Maghribi (SHAHIH: Journal of Islamicate Multidisciplinary, 2022)
Muhammad Abduh and Fazlur Rahman are among the influential Muslim scholars after the Medieval era of the eighteenth to twentieth century. Their characteristics of thought are often titled Muhammad Abduh as a Modernist and Fazlur Rahman as a Neo-Modernist. Their ideas became significant since they influenced several contemporary Muslim scholars in the Muslim world, such as Rashid Rida, Qasim Amin, Amina Wadud, Farid Esack, Nurkholis Majid, etc. This study examines the religiopolitical context of Muhammad Abduh and Fazlur Rahman in constructing their thoughts - the so-called - Modernism and Neo Modernism, followed by the comparison of both ideas. Through a comparative analysis of both scholars’ thoughts, this paper ends with some results that the Ideas of modernism and neo-modernism brought by Muhammad Abduh and Fazlur Rahman are very relevant to his religiopolitical context and in accordance with the needs of the people of that time. Modernism of the 19th century offered about being responsive to Western progress and sticking to tradition, while neo-modernism presented the response in a more systematic and methodic.